PERLINDUNGAN HAK CIPTA ATAS KONTEN REUPLOAD VIDEO YOUTUBE DI APLIKASI TIKTOK - Venturini, I Gusti Agung Ayu Gayatri Kharisma; Sawitri, Dewa Ayu Dian (Kertha Negara : Journal Ilmu Hukum, 2024)
The purpose of this study is to find out the legal protection of YouTube video copyrights that are re-uploaded on the TikTok application platform in the perspective of the Copyright Law including the responsibility of the perpetrators of YouTube video re-uploading content who have violated the rights of the perpetrator. The research method used in this study is normative juridical research, which conducts several library materials such as scientific journals, theses and other articles which contain additions from various sources related to the issues studied in this study. The study results show that someone who has re-uploaded a Youtube video on the TikTok platform violates articles 5 and 9 of the UUHC. In this case, even though the Tiktok user has included the original source, the creator is still disadvantaged economically, because there are still many people who only see the video only on accounts that re-upload the video without looking at the original source. In this case, violations that occur can be subject to sanctions listed in article 113 of the UUHC.